Sulbactam combined with tigecycline improves outcomes in patients with severe multidrug-resistant Acinetobacter baumannii pneumonia - Deng, Yanling; Chen, Lin; Yue, Mingrui; Huang, Xiaobo; Yang, Yang; Yu, Hua (BMC infectious diseases, 2022)
Background The purpose of this study was to review the treatment plan of patients with multidrug-resistant Acinetobacter baumannii (MDR-AB) pneumonia and analyze the factors associated with patient deaths and the medication regimen. Methods We collected 1,823 qualified respiratory specimens that were culture-positive for MDR-AB. 166 patients confirmed to have hospital-acquired MDR-AB pneumonia were selected as the research subjects. The differing clinical characteristics and treatment interventions between the surviving group and death group within 28 days were analyzed. Results The mortality rate was high for those aged > 75 years ( p = 0.001). Patients who underwent invasive catheter placement ( p < 0.001) and mechanical ventilation ( p = 0.046) had a higher mortality rate. Combination therapy with tigecycline can reduce the mortality rate ( p < 0.001) of MDR-AB pneumonia in patients with carbapenem-resistant AB(CRAB). Combination therapy with sulbactam was shown to reduce the mortality rate ( p < 0.001), and high-dose sulbactam (> 3 g/day) might be better than low-dose sulbactam (≤ 3 g/day). Conclusion Reducing the time of invasive catheter placement and mechanical ventilation in patients in the intensive care unit (ICU), antimicrobial treatment, combined with tigecycline and sulbactam, might help reduce the mortality rate in patients with severe MDR-AB hospital-acquired pneumonia.